AmeÌrique du Nord. - Dufour, A.-H. (Auguste-Henri), 1798-1865 (Ch. Simonneau, 1830)
Map shows political divisions and major cities for North America including the Greenland, the West Indies, and Central America; areas of Native American habitation; former Mexican state of Texas as "RepuÌblique Fredonia," Missouri, Arkansas and Columbia territories as western portion of the United States; [modern day] Alaska as "Russie Amerique." Inset: "SuppleÌment de la partie nord-ouest de l'AmeÌrique du Nord." Relief shown by hachures. Scale not given.